Variant selection in additively manufactured alpha-beta titanium alloys. (20th June 2022) - Lu, S.L.; Todaro, C.J.; Sun, Y.Y.; Song, T.; Brandt, M.; Qian, M.
Highlights: Type 2 α/α variant boundary ( [ 11 2 ¯ 0 ] / 60 ∘ ) prevails in AM Ti-6Al-4V and Ti-4Al-2V alloys with equiaxed prior-β grains, while Type 4 α/α variant boundary ( [ 10 ¯ 55 3 ¯ ] / 63 . 26 ∘ ) in AM Ti-6Al-4V and Ti-6Al-2Sn-4Z-2Mo alloys with columnar prior-β grains. Alpha-variants tend to exist as Category I triple-α clusters in equiaxed prior-β grains while as Category II clusters in columnar prior-β grains. Less significant variant selection in columnar prior-β grains leads to more uniform distribution of the 12 α phase variants than in equiaxed prior- β grains. The α/α variant boundary energy and distribution of α-variant Schimid factor can be noticeably different in AM α-β Ti alloys with columnar or equiaxed prior-β grains. Abstract: The crystallographic arrangements of the α-phase variants in α-β titanium alloys remains less identified due to the crystallographic complexity involved while being essential to understand the α-β microstructural intricacy. To improve the current understanding, specimens of two columnar-grained α-β Ti alloys (Ti-6Al-4V and Ti-6Al-2Sn-4Zr-2Mo) and two equiaxed-grained α-β Ti alloys (Ti-6Al-4V and Ti-4Al-2V) were fabricated by laser metal powder deposition (LMD). Electron backscatter diffraction (EBSD) analyses were applied to more than 10 5 α-phase variants in each alloy. The results revealed that the Type 4 α/α variant boundary ( [ 10 ¯ 55 3 ¯ ] / 63 . 26 ∘ ) is prevalent in the two columnar-grained α-β alloys while the Type 2 α/α variant boundary ( [ 11 2 ¯ 0 ] / 60 ∘ ) is common in the two equiaxed-grained α-β alloys. Further EBSD characterisation indicates that α-variant selection tends to be more prevalent in equiaxed prior-β grains, featured by the Category I triple-α-variant clusters, which mostly terminate on dense 10 1 ¯ 1 planes with lower boundary energy. Conversely, columnar prior-β grains show significant Category II triple-α-variant clusters, which mostly terminate on less dense 4 1 ¯ 3 ¯ 0 planes with higher boundary energy. Self-accommodation to compensate for the β→α transformation strain is assumed to be the major underlying mechanism. The implications of these findings for understanding the tensile strengths are discussed in conjunction with the Schmid factor of α-variants calculated in columnar- and equiaxed-grained Ti-6Al-4V. Graphical abstract: Image, graphical abstract